Disease-modifying therapeutic directions for Lewy-Body dementias - Zhang, Qiang; Kim, Youngcho; Narayanan, Nandakumar (Frontiers in Neuroscience, 2015)
Dementia with Lewy bodies (DLB) is the second leading cause of dementia following Alzheimer's disease (AD) and accounts for up to 25% of all dementia. DLB is distinct from AD in that it involves extensive neuropsychiatric symptoms as well as motor symptoms, leads to enormous societal costs in terms of direct medical care and is associated with high financial and caregiver costs. Although there are no disease-modifying therapies for DLB, we review several new therapeutic directions in treating DLB. We discuss progress in strategies to decrease the level of alpha-synuclein, to prevent the cell to cell transmission of misfolded alpha-synuclein, and the potential of brain stimulation in DLB.